Product Liability of Business Actors to Consumers Due to the Sale of Expired Food Products and Without a Distribution License - Darmayani Gita; Helsina Fransiska Pello; Husni Kusuma Dinata (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2026)
The circulation of expired food products and without a distribution permit is still a serious problem in the consumer protection system in Indonesia because it has the potential to endanger public health and safety. This study aims to analyze the regulation of product liability of business actors to consumers due to the sale of expired food products and without distribution permits based on Law Number 8 of 1999 concerning Consumer Protection, as well as to examine the legal sanctions that can be imposed on business actors. The research method used is normative legal research with a statutory approach and a conceptual approach. The source of legal materials consists of primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that consumer protection of food products is regulated through the Consumer Protection Law, Law Number 18 of 2012 concerning Food, Government Regulation Number 86 of 2019 concerning Food Safety, and regulations of the Food and Drug Control Agency regarding the distribution permit of processed foods. The concept of product liability in the Consumer Protection Law is reflected in Article 8 and Article 19 through the application of the principle of strict liability, where business actors are still responsible for providing compensation without the need to prove the existence of an element of fault first. In addition, business actors who sell expired food products and without a distribution permit can be subject to administrative, criminal, and civil sanctions. The regulation of product liability in the Consumer Protection Law aims to provide legal certainty, protection, and a sense of security for consumers against food products circulating in the community.